The 1994 Mexican Economic Crisis : The Role of Government Expenditure and Relative Prices - Kalter, Eliot (IMF Working Papers; Working Paper, 1999)
This paper discusses the role of a country's fiscal stance in weakening the financial underpinnings of an open economy with a quasi-fixed nominal exchange rate, even where the overall fiscal deficit remains unchanged, or even narrows. The paper cites the role of expanding government operations in reducing the relative price of traded goods. A marked increase in government expenditure and taxation is associated with increased production costs, excess demand for nontraded goods, and a deterioration in the financial health of the traded goods sector. The paper demonstrates that, in contrast to the current economic situation in Mexico, the period leading to the 1994 crisis closely parallels these stylized facts.